PENGEMBANGAN PENILAIAN BERORIENTASI HOTS: UPAYA PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA DI ERA GLOBAL ABAD KE-21 - I Wayan Gunartha (Widyadari, 2024)
This research aims to: 1) provide in-depth knowledge to teachers about the concept of HOTS-oriented assessment; 2) improve teachers' ability to develop HOTS-oriented assessment. This research is a literature research, with data sources are journal articles, reference books, modules, the internet, and other relevant sources. The study was conducted from October 2023 to February 2024. Data was collected by documentation and observation techniques. The research data were analyzed using exploratory descriptive methods. The results of data analysis are: 1) Higher-order thinking skills are the ability to think not just to remember, but the ability to analyze, evaluate, and create; 2) HOTS-oriented assessment has the characteristics of a) measuring higher-order thinking skills, b) contextual problem-based, c) using various question forms, d) divergent, and e) using multirepresentation. The steps for developing HOTS-oriented questions are a) analyzing basic competencies (KD), b) compiling a grid of questions, c) choosing an interesting and contextual stimulus, d) writing question items according to the question grid, and e) making scoring guidelines (rubrics) or answer keys. The benefits of HOTS-oriented assessment are: a) improving student achievement of learning outcomes, and b) increasing student learning motivation